Perbandingan Antara Solar Cell Tipe Monocrystaline Dan Polycrystaline Pada Keadaan Terhalang Untuk Pertimbangan Pemilihan Pembangkit Tenaga Surya - Wardani, Ayusta Lukita (ReTII, 2019)
The Awareness of the importance of choosing the type of power plant that is environmentally friendly makes the use of solar cells has increased through the years. There is not adequate information to choose which is better between solar cells with Monocrystalline or Polycrystalline types so that it is difficult to determine what type will be installed with the weather and the characteristics of the area that is attached to the solar power plant. So this research will compare between Monocrystalline and Polycrystalline with different conditions. Between the conditions without obstacles with conditions that have obstacles water, sand, and leaves. From the results of the research found that for conditions without obstacles that have better power is the type of Monocrystalline while for conditions having obstacles and by changes in weather characteristics is Polycrystalline.